PRINSIP PENTING PUBLIKASI ILMIAH DAN PENCEGAHAN FALSIFIKASI FABRIKASI - Vina Eka Aristya; Taryono Taryono (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study is to identify the important principles of publishing scientific research results, benefits, and systematic review of the constraints and solutions of scientific publications. The discussion of this research focuses on scientific errors in the form of falsification and fabrication. The identification of violations of scientific data distortion includes the character, causes, and prevention perspectives through a holistic approach.The research method used is qualitative research with the type of library research using keywords, namely scientific publication, manuscript, falsification, and fabrication. This study involved a systematic literature search from the online publishing database sources Sciencedirect, Web of Science, Scopus, and Google Scholar to find relevant articles published from 2000 to 2020. The study was conducted in September 2020. An electronic search revealed that there were 896 scientific publications published. relevant, of which 42 manuscripts are included in the bibliography. The synthesis of published data that was drawn was sourced from 88% of primary journals from all references, each of which was identified regarding the validity of the data for writing papers. A prospective design was used to maximize the homogeneity of the information extracted from the selected studies, as part of the research instrument.The results of the study found that the obstacles to scientific publications included the quality and novelty of research results, limited English skills, and minimal writing skills. Repeated violations of scientific thought include falsification and fabrication. This scientific error leads to distortion of research data. Individual falsification and fabrication errors are caused by unethical behavior, violations of applicable scientific norms and ethics.